The Predictive Factors for Severe Leptospirosis Cases in Kedah - Rakesh Singh Sandhu; Halim Bin Ismail; Mohd Hasni Bin Ja’afar; Sanjay Rampal (Tropical Medicine and Infectious Disease, 2020)
Over the past decade, increased awareness about leptospirosis disease in developing and industrialized countries has resulted in increased numbers of leptospirosis cases being reported worldwide. About 5% to 15% of leptospirosis patients end up with severe forms of the disease. Complication due to leptospirosis requires monitoring, specific treatments, and intensive care admission, thus increasing the cost of treating severe leptospirosis cases. Currently, we have data on incident and mortality rates, but we do not have data on the number of patients with severe form of leptospirosis or how many patients have complications, and whether or not these complications were resolved. Therefore, we carried out this study to determine the predictive factors for severe leptospirosis cases in Kedah. We conducted a cross-sectional study. The data of patients diagnosed with leptospirosis were obtained from the surveillance unit, Kedah Health Department, through the e-notification system. These data were then sorted according to the hospitals where the patients were admitted. The patients’ medical records were collected, and their information was obtained using a checklist. A total of 456 confirmed leptospirosis cases were included in the study, with 199 patients classified as severe cases and 257 patients as mild cases, based on the Malaysian leptospirosis guidelines. Most patients were male (71.5%) with a mean SD age of 36.62 ± 20.75 years. The predictive factors for severe leptospirosis include abnormal lung sounds (OR: 3.07 [CI 1.58–6.00]), hepatomegaly (OR: 7.14 [1.10–45.98]), hypotension (OR: 2.16 [1.08–4.34]), leukocytosis (OR: 2.12 [1.37–3.29]), low hematocrit (OR: 2.33 [1.43–3.81]), and increased alanine aminotransferase (SGPT ALT) (OR: 2.12 [1.36–3.30]). In conclusion, knowing these predictive factors will help clinicians identify severe leptospirosis cases earlier and develop their treatment plans accordingly, to reduce the complications and death from severe leptospirosis.